The Meaning of Suicide Attempts by Young Adults - Everall, Robin D. (Canadian Journal of Counselling and Psychotherapy, 2007)
Suicidal behavior among young adults is a significant social and psychological problem, however, little research explores its meaning from the suicidal individual's perspective. A qualitative study identified common themes and personal meanings that characterized the experiences of young adults who had made one suicide attempt between ages 20 to 24. Six major themes identified were (a) family experience (b) adolescent interactions, (c) emotional experiences, (d) self-destructive behaviors, (e) depression, and (f) perception of control. Suicidal attempts were viewed from the perspective of a continuous process that encompassed the individual world view and experiences rather than as isolated events.